Words fail : theology, poetry, and the challenge of representation - Dickinson, Colby (Perspectives in continental philosophy, 2016)
"This book investigates the form of spirituality given shape in the intersection of poetics and theological-philosophical reflection, concerned especially with matters of representation and failure"--